Micromachining using electrochemical discharge phenomenon : fundamentals and applications of spark assisted chemical engraving - Wüthrich, Rolf; Ziki, Jana D. Abou (Micro & nano technologies., 2014)
Micro-machining is an advanced manufacturing technique of growing importance, and adoption of micro-machining using electrochemical discharges (Micro-ECDM) has increased steadily in recent years. Among new developments is the interest of industry in Micro-ECDM. However, the potential of the technology is not being fully utilized and there is no comprehensive reference book available today covering it. Micromachining Using Electrochemical Discharge Phenomenon, Second Edition fills this gap. It is unique in its detailed coverage of all aspects of the Micro-ECDM process, as well as Spark Assiste.